The incidence and impact of Human Papillomavirus in HIV infected transplant patients - Botha, Janie (Department of Surgery, 2018)
Background: Human Papillomavirus (HPV) is a common sexually transmitted infection, associated with condylomata acuminata, anogenital squamous intraepithelial lesions, and ultimately invasive squamous cell carcinoma. HPV types 16 and 18 are the most common subtypes in individuals with cervical cancer. The association with these two subtypes in individuals with squamous carcinoma of the anus is fundamentally the same as with cervical cancer, and also affects the same high risk phenotype. Human imunnodeficiency virus (HIV) positive transplant patients have two modes of immunosuppression - the disease itself and the additional immunosuppression required after transplantation, which intuitively places them at a higher risk for this type of infection, if compared to their HIV negative counterparts. Aim: The first aim is to determine the prevalence of HPV-associated cytological and pathological abnormalities of the anus in HIV positive kidney transplant recipients and the second aim is to determine if HIV positive solid organ recipients carry higher risk for having HPV of the anus than HIV negative solid organ recipients. Materials and methods: This is a cross sectional study, conducted at the Transplant unit of Groote Schuur Hospital. 14 HIV positive renal transplant recipients and 14 age matched HIV negative renal transplant recipients with similar immunosuppression regimens and time from transplantation were selected. Ethical approval for the study was obtained from the UCT Ethics committee (HREC/REF: 595/2014). Informed consent was obtained from all participants. Samples for cytology and histology were taken from the anal canal. Demographic data was collected, date of HIV diagnosis, duration on anti-retroviral drugs, time since transplant, type of immunosuppression, whether there was visible condylomata or not and if there were any lesions suspicious of cancer. Cytology and histology was correlated with clinical findings. The statistics were analysed with Stata® software. Results: Mean age was 40.8y ±7.5 (range 27-52) in the HIV positive study group and 41y ±14.4 (range20-62) in the HIV negative control group. HIV positive patients were screened 40.1 months ± 21 (range 13-74.6m) post renal transplant. HIV negative patients were screened 55.9 months ± 23.3 (range 8.9-80 m) post renal transplant. Two HIV positive patients had anal warts, compared to 1 in the HIV negative group. No statistically significant difference could be demonstrated between the occurrence of intra-epithelial neoplasm on cytology in the HIV positive and negative groups. However, HIV positive patients had a higher incidence of HPV on histology that was statistically significant. There was no evidence of squamous intra-epithelial neoplasm found on histology in either group. Conclusions: Evidence of HPV of the anus was demonstrated in both groups, there was no demonstrable statistical significance in occurrence between the two groups' cytology. Histology, however, yielded a significant number of patients with HPV in the HIV positive group. None of the patients had evidence of invasive malignancy.